Quality of human spermatozoa: relationship between high‐magnification sperm morphology and DNA integrity. (22nd May 2013) - Maettner, R.; Sterzik, K.; Isachenko, V.; Strehler, E.; Rahimi, G.; Alabart, J. L.; Sánchez, R.; Mallmann, P.; Isachenko, E.
Summary The aim of this work is to establish the relationship between the morphology of Intracytoplasmic Morphologically Selected Sperm Injection (IMSI)‐selected spermatozoa and their DNA integrity. The 45 ejaculates were randomly distributed into three treatment groups: normozoospermic, oligoasthenozoospermic and oligoasthenotheratozoospermic samples. The evaluation of DNA integrity was performed using the sperm chromatin dispersion test. It was established that DNA integrity of spermatozoa is strongly dependent on ejaculate quality (P < 0.05). The count of spermatozoa with nonfragmented DNA in normozoospermic samples was high and independent from IMSI‐morphological classes (Class 1 versus Class 3, respectively) (P > 0.1). With decreased ejaculate quality, the percentage of spermatozoa with nonfragmented DNA decreased significantly (P < 0.05) independent from morphological class. Nevertheless, the rate of IMSI‐selected spermatozoa with fragmented DNA within of Class 1 in normozoospermic (Group 1), in oligoasthenozoospermic (Group 2) and in oligoasthenotheratozoospermic (Group 3) samples was 21.1%, 31.8% and 54.1%, respectively. In conclusion, there is a direct relationship between morphological parameters of spermatozoa and their DNA integrity. However, the IMSI technique alone is not enough for the selection of spermatozoa with intact nuclei.